A COMPARATIVE STUDY ON AWARENESS TOWARDS GLOBAL WARMING AMONG LAW STUDENTS - Upadhyaya, Bhawana; Upadhyaya, Dr. Bhawana; Upadhyaya, Bharat (Innovare Journal of Education, 2016)
During the past few years, earth's climate has been noticed to be getting hotter and hotter, year after year which is caused mainly due to the deterioration of our environmental quality. Continuous industrialization, development of various transportation, and deforestation, increase much SO2 and CO2 gases which augment global warming. The changes of global warming is visible from the highest mountains to deep in the oceans and it extinguished different parts ofÂ the earth and it's also creates rich bio-diversity. To identify the level of awareness towards global warming among Law students, the authors decided to conduct the present research study. A self made tool (global warming awareness study scale) made by investigators, was used for collecting the data from Law students. The result shows that male and female, rural and urban law students are well aware about global warming and they do not differ significantly towards global warming awareness.